A severe case of Ramsay Hunt Syndrome treated with acupuncture and related techniques. (May 2020) - Giralt Sampedro, I.; Carvajal, G.; García-Janeras, A.; Fabà, A.; Nishishinya Aquino, M.B.
Abstract: Ramsay-Hunt syndrome presents with a vesicular eruption in the ear canal or oral cavity associated with ipsilateral peripheral facial paralysis. The cause is reactivation of the herpes zoster virus in the geniculate ganglion. It is the second most frequent cause of non-traumatic peripheral facial paralysis. Acupuncture is a medical procedure endorsed by the WHO with a wide range of indications. It consists of the application of very fine needles in certain points of the body to relieve pain and relieve certain diseases. We present a case of a young woman with unilateral facial paralysis as part of Ramsay Hunt syndrome. She received conventional treatment with acyclovir, analgesics, corticosteroids and eye protection measures 48 h after the onset of symptoms. At three weeks, due to the lack of improvement of the facial paralysis, manual acupuncture was started along with electroacupuncture, plum blossom hammer for facial stimulation and Chinese herbal medicine. An almost complete improvement was obtained at 14 weeks since the onset of the condition. Acupuncture and related techniques may be an effective intervention for this type of condition, and are associated with very few adverse effects. Highlights: The Ramsay-Hunt syndrome is the second most frequent cause of non-traumatic peripheral facial paralysis. If the treatment does not start quickly the Ramsay-Hunt syndrome can leave sequels in the facial area. These non conventional treatments can be effective for the sequels with none or very few and light adverse effects.